Auto-luminescence in seedlings: possible indicators for the gravimetric tide? - Gallep, Cristiano de Mello (Frontiers in Photonics, 2024)
Germinating seedlings emit light in the visible range spontaneously, and these emissions are related to metabolism and reactive-oxygen species (ROS) processes. Several series of germination tests had such biological auto-luminescence (BAL) recorded in controlled conditions, fostering applications for the non-invasive, real-time evaluation of a seedling’s germinability and vigor when submitted to chemical and/or physical perturbations. However, long-term analysis of the BAL time-series of control samples conducted in different locations around the globe reveals that their BAL signals (and thus their metabolism) appear to follow the local gravimetric tide (g-tide) time profile. This indicates that the small daily and monthly variations in gravity acceleration due to the relative positioning of the Sun and Moon with respect to the Earth’s surface influence these signals. The gravimetric tide is a natural phenomenon that affects all things, fluid or solid, and is an uncontrollable variable in normal laboratory settings on Earth’s crust. All things on Earth have evolved under these pervasive cycles, with periods ranging from ∼12.2 h up to 28 d, which correspond to the Moon cycle. Tide-like cycles occur in living beings of different types, from the simplest bacteria to the most complex human beings, and we speculate that water availability at the molecular level could be a significant physical factor in modulating bio-activity by enabling protein folding and all metabolic pathways that require a synchronized organization to adapt to external environmental conditions. In this study, we summarize published results of a seedling’s BAL with cycle patterns resembling the g-tide in Limeira/BR, Prague/CZ, Leiden/NL, and Hamamatsu/JP and discuss the possible implications of this phenomenon for chronobiological studies.